London: opening the archive to what was never written: Iain Sinclair and the transformative magic of the walk - Rodríguez Iborra, Susana (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
In the face of an evident institutional obliviousness and in dialogue with contemporary historical debates between history and memory, we ask ourselves how literary memory works for historical knowledge by proceeding to an intertextual dialogue of some significant fragments of London: City of Disappearances, Living with Buildings and Walking with Ghosts or The last London by Iain Sinclair in dialogue with other textual fragments of Walter Benjamin's Theses on the Concept of History. From this textual constellation , we will try to see how this author allow us to inhabit heterotopic spaces where we can read asynchronous time in a synchronic way and, in this way, break with the continuum of the empty time of progress, allowing us to live an aesthetic experience that takes charge of the traces that the official discourse has left on the margins and that still demand historical justice.
Keywords: Memory, History, archive, Sinclair, intertextuality.